Increasing Student’s Understanding on Adolescent Reproductive Health Trough the Crossword Puzzle Media and Learning Videos Aided Counseling - Wijayanti, Erna; Rahmawati, Titik; Syaroni, Mokh; Arafat, Ahmad Tajuddin; Saadah, Ira Naila; Purnamaningrum, Arifah; Rasyida, Nisa (LP2M of Institute for Research and Community Services - UIN Walisongo, 2023)
Adolescence is important for students because it transitions from childhood to adulthood. Knowledge about changes in adolescence, especially adolescents in Islamic boarding schools regarding adolescent reproductive health, is still low, so it needs to be improved. This service aims to increase the knowledge of service partners, especially students in Islamic boarding schools, regarding adolescent reproductive health. This devotion used the ABCD method, which consists of five stages: inculturation, discovery, design, definition, and reflection. This service program is carried out in July–August 2022. Service partners are students from classes X, XI, and XII. The service program is carried out with a learning model of team games tournaments (TGT) assisted by crossword puzzles and learning videos. Service data were obtained using pre- and post-tests regarding adolescent reproductive health. The data obtained are analyzed qualitatively and descriptively. The service results showed that counselling activities using crossword puzzle media and learning videos increased the knowledge of service partners by an average of 8.41.